2014
DOI: 10.3109/13880209.2014.892513
|View full text |Cite
|
Sign up to set email alerts
|

beta-Adrenoreceptor antagonists reduce cancer cell proliferation, invasion, and migration

Abstract: Beta2-AR antagonist seemed to be the most cytotoxic β-blocker on non-stimulated cancer cells. Propranolol and ICI118,551 were more effective than atenolol in inhibiting invasion and migration of non-stimulated MCF7 and HT-29 cells; ICI118,551 being the most potent. Concordantly, β2-selective blockage seemed to be more effective for non-stimulated cells. Effect of the selective β-AR antagonists showed variation depending on the concentration, incubation time, and histological origin of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…2). These results appear to be consistent with those of preclinical studies suggesting that the effects of beta-adrenergic signaling on tumor progression and metastasis are inhibited by the β2-receptor antagonists but not by β1 antagonists [1824]. Consequently, better designed observational studies or randomized controlled trials are required before this type of beta-blocker can be considered as a therapeutic option for patients with breast cancer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…2). These results appear to be consistent with those of preclinical studies suggesting that the effects of beta-adrenergic signaling on tumor progression and metastasis are inhibited by the β2-receptor antagonists but not by β1 antagonists [1824]. Consequently, better designed observational studies or randomized controlled trials are required before this type of beta-blocker can be considered as a therapeutic option for patients with breast cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies has demonstrated that beta-2 adrenergic signaling plays a role in several pathways involved in breast tumor progression and metastasis [17, 18], but others have found that beta-adrenergic receptor (AR) stimulation may both inhibit and promote breast tumor growth [1923]. A recently published study adds further to the body of evidence on the effect of agonist type, indicating that the beta 2-AR antagonist in particular seems to be the most cytotoxic beta-blocker in non-stimulated cancer cells [24]. However, the majority of clinical observational studies carried out to date have focused on comparing the association between the use of propranolol or atenolol and breast cancer risk or mortality and have not explored the relationship between the subtype of beta-AR expression and breast cancer risk [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison between PRO and the selective beta adrenergic receptor antagonists atenolol (beta1) and ICI118-551 (beta 2), Işeri and colleagues showed that PRO and ICI118,551 were more potent in reducing the proliferation, migration, and invasion of non-stimulated breast (MCF7), colon (HT-29), and hepatocellular (HepG2) cancer cells than atenolol [101]. …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In contrast, there have also been contradictory results, for example for breast cancer where Pérez Piñero et al have reported that beta adrenergic agonists isoprenaline and salbutamol reduced breast tumour growth in animal models, and that PRO treatment reversed this inhibition [102] and other authors have reported a decrease in proliferation in breast cancer cell line, for example in the MCF7 cell line [101]. …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Our labs have spearheaded efforts to examine the mechanism of action and clinical use of β-blockers against tumors and have reported that β-blockade disrupts proliferation, survival, migration, cell-to-matrix attachment, and global transcriptional expression patterns in vascular tumors including infantile hemangiomas and angiosarcomas [1923]. Other labs have shown that β-AR signaling affects epithelial-to-mesenchymal transition [24] and β-blockade reduces tumor angiogenesis, cell proliferation, migration, and invasion [2530]. Our labs and others have translated these retrospective and preclinical studies into the clinic to report that use of the β-blocker propranolol in patients with lethal angiosarcomas results in decreased tumor proliferation and sustained therapeutic responses [3133].…”
Section: Introductionmentioning
confidence: 99%